2022
DOI: 10.1515/reveh-2021-0129
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to air pollution and risk of ovarian cancer: a review

Abstract: Objectives Exposure to air pollution has destructive health consequences and a potential role in ovarian cancer etiology. We conducted a systematic review of the studies assessing the associations between ovarian malignancy and exposure to air pollutants. Content The included studies were categorized based on types of measured ambient air pollutants, including particulate matter (five studies), gases (two studies), air pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…In a Taiwanese study, the association between PM 2.5 on the municipality level and mortality rates for ovarian cancer was likewise significant 43 . Other studies from outside the USA finding an association between ovarian cancer mortality and pollution have included other pollutants besides particulate matter or have focused on specific populations with increased occupational exposures 42,45,53 . A study that used the SEER registries to look at the incidence of all cancer types did not find a significant association between PM 2.5 and ovarian cancer incidence 34 .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In a Taiwanese study, the association between PM 2.5 on the municipality level and mortality rates for ovarian cancer was likewise significant 43 . Other studies from outside the USA finding an association between ovarian cancer mortality and pollution have included other pollutants besides particulate matter or have focused on specific populations with increased occupational exposures 42,45,53 . A study that used the SEER registries to look at the incidence of all cancer types did not find a significant association between PM 2.5 and ovarian cancer incidence 34 .…”
Section: Discussionmentioning
confidence: 93%
“…43 Other studies from outside the USA finding an association between ovarian cancer mortality and pollution have included other pollutants besides particulate matter or have focused on specific populations with increased occupational exposures. 42,45,53 A study that used the SEER registries to look at the incidence of all cancer types did not find a significant association between PM 2.5 and ovarian cancer incidence. 34 However, this study was time-independent and did not account for the lagging exposure to PM 2.5 , and employed a different methodology to create a spatial raster prediction surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ambient PM air pollution is also related to a higher incidence of thyroid cancer ( 65 ). Moreover, other studies have revealed that the chronic exposure to air pollution may produce alterations in normal ovarian function e.g., estrogen-like effect or gene mutation, which can lead to ovarian cancer ( 66 ). Additionally, transplacental exposure to PM is connected to higher placental mutation rate and such epigenetic alterations may be a reason for placental carcinogenicity ( 55 ).…”
Section: Endocrine Disrupting Effects Of Particulate Matter (Pm ...mentioning
confidence: 99%